First principle modeling and simulation of hydrogen interaction with carbon nanotubes - Ren, Yunxia (2008)
The work presented in this thesis addresses the issues concerning the use of carbon nanotube as a storage media for hydrogen. The work is theoretical modeling and simula-tion based, and it attempts to make sense of vast and scattered experimental data reported in the literature with regard to the storage capacity, some so severe such that reported re-sults are unrepeatable by other groups. In the thesis, we provide the ab initio theoretical framework for describing the underlying basic mechanism governing the physisorption and chemisorption processes of hydrogen on and into carbon nanotubes. We introduce the mul-tiscale ONIOM scheme for this study, which overcomes the difficulties when using stand-alone methodologies which many researchers are currently applying. These are either too coarse and therefore unable to capture the reaction processes with low level methods, or too compute intensive when higher level methods are used.